1977
DOI: 10.3109/14017437709167818
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Vascular Ring with Clinical Manifestations

Abstract: A clinical follow-up study was performed in 11 unoperated patients with symptoms due to vascular ring. The age at diagnosis was 2-48 months (mean 13 months); 7 of the patients were less than 12 months old. The follow-up time varied between 1 and 22 years (median 7 years). Nine patients were entirely free of symptoms, which they had outgrown in the course of 1-2 years after the diagnosis was made; none of these 9 had symptoms after the age of 4 years. Two patients had symptoms due to either oesophageal compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Previous findings have prompted support for a conservative attitude regarding surgery . As reported above, one study showed no increased risk of cardiopulmonary decompensation under defined exercise, hence discouraging operation of asymptomatic patients with ARSCA .…”
Section: Discussionmentioning
confidence: 90%
“…Previous findings have prompted support for a conservative attitude regarding surgery . As reported above, one study showed no increased risk of cardiopulmonary decompensation under defined exercise, hence discouraging operation of asymptomatic patients with ARSCA .…”
Section: Discussionmentioning
confidence: 90%
“…Of these patients, six required medical treatment for their symptoms and eventually had complete resolution of their symptoms as did the remaining five patients. No patients remained symptomatic after four years of age and there were no deaths during the reported follow-up period [7]. No such formal natural history evaluation of asymptomatic vascular rings has been published to date.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of the literature yields a total of 58 asymptomatic or unrepaired vascular rings documented over the course of 18 studies, including the current study [4,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. Table 1 summarizes the characteristics of the individual cases while Table 2 summarizes the overall characteristics of the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-7 These vascular rings and slings m a y remain asymtomatic despite the abnormality. 1,3,5,7,10 Since the first successful surgical correction of a vascular ring by Robert E. Gross, a wide anatomical variety had been documented by various authors. 1,2-6 This retrospective report reviews our experience with 15 patients with vascular compression of the trachea and esophagus treated at All India Institute of Medical Sciences, New Delhi.…”
Section: Introductionmentioning
confidence: 99%